The role of community empowerment tools in local development - Palma industrial zone in Constantine as a model - AMRANI, Said (Journal of Finance & Corporate Governance, 2020)
The aim of this research is to assess the effectiveness of community empowerment tools in changing the thinking and work of the community through participation of members of the local environment and the provision of fair public services to meet their needs. To determine this, we conducted a field study of the industrial zone of Palma in the province of Constantine. The study revealed several results, including: the importance of collective networks in providing information to industrial projects, poor public services that affect the activity of projects, as well as poor communication between projects and the Industrial Zone Management Authority